Ultrafast synthesizing nanoflower-like composites of metal carbides and metal oxyhydroxides towards high-performance supercapacitors. (10th January 2023) - Dai, Yuming; Gul, Hajera; Sun, Chao; Tan, Linghua; Guo, Yue; Raza, Waseem; Hussain, Arshad; Pan, Jiachen; Azam, Mudassar; Zhu, Wenhui; Chen, Boyu; Chen, Yuju; et al.
Highlights: The 3D nanoflower-like F-MXene/CoOOH composites were prepared by an ultrafast method. The gravimetric specific capacitance of 955.08 C/g was achieved at 5 mV/s. The capacitance retention rate was as high as 84.1% after 100, 000 cycles at 1 A/g. Abstract: Because of their outstanding electrochemical performance and high theoretical specific capacity, metal oxyhydroxides or metal hydroxides have been paid significant attention as electrode materials for supercapacitors. Unfortunately, because of their poor conductivity, the experimental capacity is considerably lower than the theoretically expected value. Similarly, the use of 2D transition metal carbides (MXene) in energy storage electronic devices has also drawn research attention. However, its self-restacking makes it difficult for electrolyte ions to reach the material's active sites. Therefore, in this research work, an ultrafast one-step method for the synthesis of 3D nanoflower-like MXene/metal oxyhydroxide composites has been proposed. Composite materials synergistically combine the high theoretical capacity of metal oxyhydroxides with good electrical conductivity of MXene, resulting in excellent supercapacitive performance. The resulting composite delivered the highest specific capacity of 955.08 C/g at a scan rate of 5 mV/s and its maximum energy density of 32.13 Wh/kg is attained at a power density of 324.97 kW/kg due to synergistic combination of MXene and metal oxyhydroxides. Furthermore, the capacity retention rate at 1 A/g current density is as high as 84.1% after ultralong 100, 000 cycles. Due to the excellent performance of synthesized 3D nanoflower-like MXene/metal oxyhydroxide composites, it can be used for electrode materials fabrication with enhanced energy storage properties for supercapacitors to fulfill energy needs. Graphical abstract: Image, graphical abstract